THE EFFECT OF HUMAN CAPITAL, ENTREPRENEURSHIP ORIENTATION AND MARKET ORIENTATION ON COMPETITIVE ADVANTAGE (CASE STUDY ON HOSPITALITY INDUSTRY IN CENTRAL JAVA) - Ricky Yohanes; Retno Hidayati (Jurnal Apresiasi Ekonomi, 2019)
This study aimed to determine the effect of human capital, entrepreneurial orientation and market orientation on competitive advantage in the hospitality or hotel service industry in Central Java. The method of data collection is done through a questionnaire. The population in this study are all lodging or hotel service business people in Central Java. there were 150 respondents involved in this study which resulted from random sampling. Data analysis was done by multiple regression. The results obtained in this study are human capital, entrepreneurial orientation and market orientation influence the competitive advantage in the hospitality or hotel service industry in Central Java. Keywords: Competitive advantage, human capital, entrepreneurial orientation, market orientation